Visual Political Communication
XXI, 288 p. 35 illus., 16 illus. in color.
Keywords: ‘This book is an innovative and timely collection that will soon become central to research and teaching on visual, digital and political communication. Through an original combination of theoretical reflections, methodological recommendations and empirical findings, this volume offers a well-rounded approach to exploring the relationship between visual images, digital technologies, and political practices. The collection’s cutting-edge case studies convincingly demonstrate the power of the visual in top-down and bottom-up politics alike.’ –Giorgia Aiello, Associate Professor in Media and Communication, University of Leeds, UK ‘At a time when political communication is increasingly dominated by visual imagery, this ground-breaking volume makes an essential intervention. It provides a comprehensive, engaging, provocative and wide range of contributions that advance knowledge in this sorely neglected, but increasingly vital area of research, and help us understand everything from the rise of Donald Trump to the strategies of the #BlackLivesMatter movement.’ –Professor Karin Wahl-Jorgensen, Cardiff University, UK ‘The theme image vs. substance is challenging scholars in the digital age. In Visual Political Communication, the contributors explore the dynamics of visual communication and the political communication process. The result is an in-depth analysis of the various ramifications of the visual in political communication, in campaigns and in government that sheds light into many disquieting phenomena we notice in modern politics worldwide.’ –Gianpietro Mazzoleni, Professor of Political Communication, University of Milan, Italy This edited volume offers a theoretically driven, empirically grounded survey of the role visual communication plays in political culture, enabling a better understanding of the significance and impact visuals can have as tools of political communication. The advent of new media technologies have created new ways of producing, disseminating and consuming visual communication, the book hence explores the theoretical and methodological underpinnings of visual political communication in the digital age, and how visual communication is employed in a number of key settings. Anastasia Veneti is Senior Lecturer in Marketing Communications at Bournemouth University, UK. Daniel Jackson is Associate Professor of Media and Communication at Bournemouth University, UK. Darren G. Lilleker is Associate Professor in Political Communication at Bournemouth University, UK.